(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Music has long been recognized not only as a cultural and artistic phenomenon but also as a powerful tool for cognitive development. In recent decades, research has increasingly demonstrated the role of musical activities in enhancing attention, memory, and executive functions in learners. This study develops and experimentally validates a pedagogical methodology designed to activate attention and memory during music lessons. The approach integrates structured rhythmic–melodic sequences, emotional engagement strategies, and multimodal learning environments to improve cognitive performance in students aged 7–13. A 12-week intervention was implemented with experimental and control groups. Quantitative results show a significant increase in sustained attention span (+36.5%) and memory retention (+41.2%) in the experimental group. Qualitative analysis reveals higher emotional engagement and reduced cognitive fatigue. The findings are interpreted through the lenses of cognitive load theory, rhythmic entrainment, and emotional memory models, emphasizing music as an effective cognitive training medium. This methodology aligns with global educational standards set by UNESCO and OECD and can serve as a practical framework for music educators aiming to enhance cognitive learning outcomes.